Modelling of Crowd Evacuation with Communication Strategy Using Social Force Model - Norhaida, Hussain; Wai Shiang, Cheah (Qazvin Islamic Azad University, 2022)
Mobile crowd steering application has received much attention nowadays to steer crowds during fire or disaster evacuation. As reported in many studies, real drill experiments have been conducted to validate the mobile crowd steering application. However, simulations have also been undertaken to overcome the limitation of practical drill experiments when testing the application. Although there are algorithms reported for agent-based mobile crowd simulations, not many studies have adopted the social notion during mobile crowd steering simulations. As mobile crowd steering applications require user interaction during fire evacuation, we have foreseen a gap in current simulation algorithms, which leads to unrealistic simulation. This paper introduced a new insight into the agent-based crowd simulation through integration of communication strategy into the state of the art of social force for crowd management. The model was presented, formulated, and validated through a fire evacuation simulation. From the simulation results, the proposed model can reduce evacuation time and crowd density at the door opening area as compared to the original Social Force Model in a similar experimental setup.